Best Answer

X intercept is the value of X when Y = 0

-5Y + 3X = 12

ley Y = 0

3x = 12

x = 4

Q: What is the x intercept of -5y plus 3x equals 12?

Write your answer...

Submit

Still have questions?

Continue Learning about Calculus

When the equation is in the form "y = mx + c" the intercept is given by 'c' (and the gradient by 'm'): 3x + 3y = 9 ⇒ x + y = 3 ⇒ y = -x + 3 ⇒ Intercept is 3 (And the gradient is -1)

3x+5y=48 5y=48-3x-3x+5y=12 -3x+(48-3x)=12-6x=-36x=65y=48-3(6)5y=30y=6(6,6)

3x - 12 = 10x - 15 - 6x -10 3x - 12 = 4x -25 3x + 13 = 4x 13 = 4x - 3x 13 = x None?

3x+12 = 18 3x = 18-12 3x = 6 x = 2

6x - 12 = 3x + 12 Add twelve to both sides.6x - 12 + 12 = 3x + 12 + 12Simplify.6x = 3x + 24Subtract 3x from both sides.6x - 3x = 3x + 24 - 3xSimplify.3x = 24Divide both sides by 3.x = 8The answer is x = 8.

Related questions

If: -3x+2y = 12 Then: y = 1.5x+6 in slope-intercept form

-3x + 2y = 12-3x + 3x + 2y = 3x + 122y = 3x + 122y/2 = 3x/2 + 12/2y = (3/2)x + 6

3x - y = 12 is the same as 3x - 12 = y, or y = 3x - 12.

3x - 2y = 12 2y + 12 = 3x 2y = 3x - 12 y = 3x/2 - 6 Gradient = 3/2 Y-intercept = -6

3x + y = 12The x intercept occurs when y = 0. Then, 3x + 0 = 12 : 3x = 12 : x = 4The y intercept occurs when x = 0. Then, (3 x 0) + y = 12 : y = 12.

3x + 6y = 12 Rearranging terms: 6y = -3x + 12 Divide through by 6: y = -1/2*x + 2

1

4

It is: 1

2

It is: y = -2/3x+4 in slope intercept form

If you mean 3x+4y = 12 then the x intercept = 4 and the y intercept = 3